Small-scale experimental and numerical simulation of blasting in jointed rock-like materials under varied joint and explosive conditions - Xuejiao Cui; Mingsheng Zhao; Hongbing Yu; Jianmin Zhou (PLoS ONE, 2025)
This study focuses on the blasting failure of rock-like materials, aiming to investigate the effect of the joint spatial characteristics and explosive parameters. Rock mass blasting is complex, and the influence of factors like lithology, rock structure, and explosive characteristics needs consideration. In similar model tests, concrete casting molds are used to prepare nine groups of joint models with different joint quantities, angles, and distances. Mixed emulsion explosives are used for blasting, and the crack expansion process and blasting fragmentation properties are analyzed. In numerical simulations, ANSYS/LS-DYNA is employed with carefully selected material parameters. The results show that the blasting effect of rock mass first increases and then decreases with joint width, increases with joint number and spacing, and first increases and then decreases with joint inclination angle. The consistency between the similar model tests and simulation results validates the conclusions of this study, providing theoretical support and practical guidance for optimizing the blasting excavation parameters of the jointed rock mass. This research offers a scientific decision-making basis for dynamic adjustments of blast schemes, safety risk pre-control, and construction efficiency optimization in engineering management.